Ameliorated effects of Lactobacillus delbrueckii subsp. lactis DSM 20076 and Pediococcus acidilactici NNRL B-5627 on Fumonisin B1-induced Hepatotoxicity and Nephrotoxicity in rats - Amira A. Abdellatef; Ashraf A. Khalil (Elsevier, 2016)
Oxidative stress has been implicated in a number of human regeneration and disease processes including atherosclerosis, pulmonary fibrosis, cancer, and different neurodegenerative diseases. The aim of this study was to evaluate the protective effects of Lactobacillus delbrueckii subsp. lactis DSM 20076 (LL-DSM) and Pediococcus acidilactici NNRL B-5627 (PA-NNRL) against the hepatic- and nephro-toxicity of fumonisin B1 (FB1) in FB1-treated rats for an experimental period of 4-weeks. Eighty mature male Sprague-Dawley rats were divided to 12 groups: 1 untreated group; 3 groups fed by a FB1-contaminated diet (50, 100 and 200 mg FB1/kg diet, respectively); 1 group fed orally by LL-DSM (1 ml/d); 1 group fed orally by PA-NNRL (1 ml/d); 3 groups co-administered by FB1-contaminated diet and LL-DSM (1 ml/d), and 3 groups co-administered by FB1-contaminated diet and PA-NNRL (1 ml/d). Malonaldehyde (MDA) nitric oxide, glutathione content, SOD activity, total antioxidant capacity (TAC), total oxidant status (TOS) and oxidative stress index (OSI) were determined. DPA assay was used to assess apoptosis in liver and kidney tissues. The animals fed with FB1-contaminated diet showed a significant increase in oxidative stress markers and DNA fragmentation accompanied with significant decrease in GSH content, SOD activity, and TAC in liver and kidney tissues, especially at high-dosage of FB1 (T200). Probiotics antioxidant strains (LL-DSM and PA-NNRL) relatively succeeded to restore almost all parameters investigated as well as to reduce DNA fragmentation in liver and kidney tissues. As a conclusion, probiotics may induce its protective role via increasing the antioxidant capacity, inhibition of lipid peroxidation, scavenging of free radicals and decreasing DNA lesions in liver and kidney of experimental animals tested.